Linking language with embodied and teleological representations of action for humanoid cognition - Lallee, Stephane; Madden, Carol; Hoen, Michel; Dominey, Peter F. (Frontiers in Neurorobotics, 2010)
The current research extends our framework for embodied language and action comprehension to include a teleological representation that allows goal-based reasoning for novel actions. The objective of this work is to implement and demonstrate the advantages of a hybrid, embodied-teleological approach to action-language interaction, both from a theoretical perspective, and via results from human-robot interaction experiments with the iCub robot. We first demonstrate how a framework for embodied language comprehension allows the system to develop a baseline set of representations for processing goal-directed actions such as “take”, “cover”, and “give”. Spoken language and visual perception are input modes for these representations, and the generation of spoken language is the output mode. Moving towards a teleological (goal-based reasoning) approach, a crucial component of the new system is the representation of the subcomponents of these actions, which includes relations between initial enabling states, and final resulting states for these actions. We demonstrate how grammatical categories including causal connectives (e.g. because, if-then) can allow spoken language to enrich the learned set of state-action-state (SAS) representations. We then examine how this enriched SAS inventory enhances the robot’s ability to represent perceived actions in which the environment inhibits goal achievement. The paper addresses how language comes to reflect the structure of action, and how it can subsequently be used as an input and output vector for embodied and teleological aspects of action.